CROSS-CULTURAL COMMUNICATION ADAPTATION STRATEGIES: STUDENT EXPERIENCE IN ASEAN COUNTRIES KKN PROGRAM Strategi Adaptasi Komunikasi Lintas Budaya: Pengalaman Mahasiswa KKN di Negara-Negara ASEAN (Thailand, Malaysia, Indonesia) - Susilo Bambang Purnama,; Srie Rosmilawati, (Journal of Innovation Research and Knowledge, 2025)
Cross-cultural communication competence is essential for students participating in international community service programs. This study examines communication adaptation strategies employed by communication students during a KKN (Kuliah Kerja Nyata) program across three ASEAN countries: Indonesia, Malaysia, and Thailand. Using a qualitative autoethnographic approach, data were collected through participant observation, field notes, and documentation during the program implementation from July to September 2024. The study reveals three primary adaptation strategies: linguistic adaptation through local language learning, non-verbal communication adjustment to cultural contexts, and intercultural empathy development. Findings indicate that successful cross-cultural communication requires flexibility, cultural sensitivity, and active observation of local communication patterns. This research contributes to understanding intercultural communication dynamics in Southeast Asian contexts and provides practical implications for international community service program design